Trait anxiety predicts disease-specific health status in early-stage breast cancer patients - Van Esch, Lotje; Roukema, Jan A.; Van der Steeg, Alida F. W.; De Vries, Jolanda (Quality of Life Research, 2011)
The objectives of this study were to examine the differences in health status (HS) of women with breast cancer (BC) at different moments in time, and between women scoring high and not high on trait anxiety, and to identify possible predictors of HS 6 and 12 months after surgery.